1998
DOI: 10.1021/ja9801947
|View full text |Cite
|
Sign up to set email alerts
|

High Helicities of Lys-Containing, Ala-Rich Peptides Are Primarily Attributable to a Large, Context-Dependent Lys Stabilization

Abstract: Peptides 1K, YKGGGAAAAAAAAKAAAAAAAAAGGGK-NH 2 ; 2K, YKGGGAAAAAKAAAAA-KAAAAAAGGGK-NH 2 ; and 3K, YKGGGAAAAKAAAAKAAAAKAAAGGGK-NH 2 have been prepared by solid-phase synthesis, purified, and characterized by amino acid analysis, MALDI mass spectrometry, and ultracentrifugation. Their circular dichroism (CD) spectra of unaggregated solutions are reported for measurements in 0.01 M NaCl at 2, 25, and 60 °C and at 2 °C in aqueous guanidinium hydrochloride (0-3 M) and aqueous trifluoroethanol (TFE, 0-15 mol %). The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
54
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 82 publications
6
54
0
Order By: Relevance
“…This force field also gives values for the helix propagation and nucleation parameters for Ala measured by Yang et al (9) but in disagreement with other experimental measurements (2, 3). Our calculations show that the Arg side chain significantly stabilizes the helix state of the Fs peptide, in agreement with Williams et al (15) and Vila et al (14). However, we also find that A21 is 34% helical at 275 K, consistent with Spek et al (8) …”
supporting
confidence: 92%
See 1 more Smart Citation
“…This force field also gives values for the helix propagation and nucleation parameters for Ala measured by Yang et al (9) but in disagreement with other experimental measurements (2, 3). Our calculations show that the Arg side chain significantly stabilizes the helix state of the Fs peptide, in agreement with Williams et al (15) and Vila et al (14). However, we also find that A21 is 34% helical at 275 K, consistent with Spek et al (8) …”
supporting
confidence: 92%
“…Within the Lifson-Roig (10, 11) and Zimm-Bragg (12) models for the helix-coil transition, the intrinsic propensity of an amino acid to form a helix is a measure of the interactions of the amino acid with its own and nearest-neighbor amino acid backbone (11,13). Theoretical (14) and experimental studies on prenucleated synthetic peptides (15) have suggested that the high helical propensity of Ala-containing peptides is a consequence of the neighboring side chains and is an effect extrinsic to the Ala side chains. Specifically, Vila et al (14) have argued that the high helical propensity of Ala-rich peptides containing large charged side chains is stabilized by the effect of the side chains in reducing the accessibility of the peptide backbone to water.…”
mentioning
confidence: 99%
“…In the CD investigations reported here, there is no indication that A3 or B6 shows a similar conversion to β-sheet; their temperature-dependent conformational behavior is similar to that of other previously reported alanine-rich peptides. 23,24,57,58 The thermal stability of the protein polymers at higher concentrations of 1 mg/mL in pH 2.3, 10 mM phosphate buffer was also monitored via differential scanning calorimetry. Figure 3a shows the calorimetric data for both A3 and B6 at a scan rate of 60 °C/h.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was proposed that alcohol may act on the exposed CO and NH groups by diminishing their exposure to the solvent, i.e., shifting the conformational equilibrium toward more compact structures, such as ␣-helical conformation (23). An alternative proposal for shifting the helix-coil equilibrium of polyalanine toward an ␣-helical conformation is to introduce charged residues into the sequence (48,49); however, in this case, the tendency to form the ␣-helix should not be associated with the ␣-helical propensity of alanine discussed herein.…”
Section: Resultsmentioning
confidence: 99%